Predictors of hip fracture mortality at a general hospital in South Brazil: an unacceptable surgical delay - Tiango Aguiar Ribeiro; Melissa Orlandin Premaor; João Alberto Larangeira; Luiz Giulian Brito; Michel Luft; Leonardo Waihrich Guterres; Odirlei André Monticielo (Clinics, 2014)
OBJECTIVE: Hip fractures have been associated with increased mortality in the elderly. Several risk factors such as the time between the insult and the surgical repair have been associated with hip fracture mortality. Nevertheless, the risk of delayed surgical repair remains controversial. Few studies have examined this issue in Brazil. The aim of this study was to study the risk factors for death one year after hip fracture and in-hospital stay at a tertiary hospital in South Brazil. METHODS: A prospective cohort study was carried out from April 2005 to April 2011 at a tertiary university hospital at Santa Maria, Brazil. Subjects admitted for hip fracture who were 65 years of age or older were followed for one year. Information about fracture type, age, gender, clinical comorbidities, time to surgery, discharge, and American Society of Anesthesiologists score were recorded. Death was evaluated during the hospital stay and at one year. RESULTS: Four hundred and eighteen subjects were included in the final analysis. Of these, 4.3% died in-hospital and 15.3% were dead at one year. Time to surgery, American Society of Anesthesiologists score, Ischemic Heart Disease, and in-hospital stay were associated with death at one year in the univariate analysis. The American Society of Anesthesiologists score and time to surgery were one-year mortality predictors in the final regression model. In-hospital death was associated with American Society of Anesthesiologists score and age. CONCLUSION: Time to surgery is worryingly high at the South Brazil tertiary public health center studied here. Surgical delay is a risk factor that has the potential to be modified to improve mortality.